Incorporation of solar energy in water technologies: solar desalination for the provision of water in remote areas - Blanco Gálvez, Julián (2010)
The XX century has brought an unprecedented development in the history of humanity with impressive advances in all disciplines of science and technology. But these progresses have not been something free, but have had a price that would not be unreasonable to consider that, under certain prisms, has been excessive. During the past 100 years, the human population on earth has increased by a factor of 4 (from 1600 million in 1900 to over 6,000 million today). However water consumption has increased by 9 in the same period and power consumption by 16, and therefore associated with a degradation of the environment and natural resources in general, very significant. Keywords.-